THE CHARACTERISTICS OPERATIONAL COST OF FREIGHT TRANSPORT IN SOUTH SULAWESI PROVINCE - INDONESIA - Hakzah Hakzah; Muhammad Isran Ramli; Andi Irmayani Pawelloi (Universitas Mercu Buana, 2021)
Infrastructure development of the freight transport system has a vital position in accelerating Indonesian economic growth. This study aims to analyze one of the dominant characteristics of freight transportation, namely freight transportation costs in South Sulawesi Province. A questionnaire-based interview survey of operators was conducted to determine operator characteristics, vehicle characteristics, trip characteristics, and commodity characteristics. They are analyzing data using a descriptive statistical approach, building a cost and distance relationship model using a regression model approach while analyzing the priority of freight transport selection using an Analytical Hierarchy Process (AHP). An AHP is a decision-making model with multiple criteria. The analysis shows that the high costs are the component costs of the operator’s salary, fuel costs, and vehicle maintenance costs. Operating cost modelling provides a good level of models, both in terms of modes and commodities transported. In contrast, the travel time model based on modes and types of commodities shows inefficient. Based on the results, the pickup mode is optimal in cost and travel time with a weight of 39.8% and 50.3%. Trucks 3-4-5 Axles are the optimal mode of transportation when viewed in terms of distance (58.8%) and transportation volume (65.5%). In contrast, the two Axles Truck has characteristics between Pickups and 3-4-5 Axles Trucks. This result is better developed for a more comprehensive model of the cost of freight transport in South Sulawesi Province, Indonesia.